Agents and Third-Party Recruiters in International Higher Education - Altbach, Philip (International Higher Education, 2011)
In today's globalized world, higher education is a big business. There is a dramatic proliferation of third-party recruiters and agents who recruit prospective students as well as provide general information about studying abroad. These agents are impairing the standards and integrity of higher education because of monetary incentives. Also, there is no stated qualification for them. The solution is to abolish them, and provide objective by encouraging universities to provide accurate information.